The Geography of Contemporary China - Wang, Jing'ai.; Liang, Shunlin; Shi, Peijun (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook provides a comprehensive and very detailed insight into Chinese Contemporary Geography in English. It documents the geographical issues associated with China's rapid growth. Since initiating the reforms and open policy, China has achieved tremendous success. China's rapid growth is now a driving force in the global economy and is achieving unprecedented rates of poverty reduction. However, China also faces a number of sustainability and emerging challenges associated with rapid growth such as growing regional disparities in terms of per capita income and social-economic development, sustainable resource development, and issues related to regional and global economic integration. In addition, rapid economic growth has also brought about major challenges such as resource shortages, ecological and environmental destruction, land degradation and frequent disasters. This book presents the authors' reflections. This lavishly illustrated book covers physical geography, history, and economic and political systems of the world's most populous country. The major focus is on geographical issues in China's contemporary development: agriculture, population, urbanization, resource and energy, and environment. The lead author of the book has taught relevant courses in China for three decades, and authored and edited multiple textbooks for Chinese students. This book will appeal to undergraduate students of geography and related disciplines with a regional focus on China and to the general reader who wants to learn different geographical aspects of modern China with little academic background in geography.
Chapter 1. Introduction -- Chapter 2. Territory and Geopolitics -- Chapter 3. Topography and Landforms -- Chapter 4. Climate and Climate Change -- Chapter 5. Hydrology and Water Resources -- Chapter 6. Land Cover and Land Use -- Chapter 7. Natural Resources and Energy -- Chapter 8. Land Degradation and Ecological Restoration -- Chapter 9. Environmental Pollution and Protection -- Chapter 10. Natural Disasters -- Chapter 11. Population and Urbanization -- Chapter 12. Economic Geography -- Chapter 13. China's Opening-up and Trade -- Chapter 14. Tourism Geography -- Chapter 15. Sustainable Development -- Index.
Keywords: Geography; Physical geography; Human geography; Environment; Asia-Politics and government; Cultural geography; Regional Geography; Physical Geography; Human Geography; Environmental Sciences; Asian Politics; Social and Cultural Geography